The Implementation of the Word Guessing Method in Stimulating Students' Memory in Grade V Science and Social Studies (IPAS) at MI Al-Ba’ani, Bengkulu City - Triyani Triyani; Rizki Aditya Kumara; Khermarinah Khermarinah; Ajat Manjato (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to describe the implementation of the word guessing method in stimulating students' memory during Science and Social Studies (IPAS) learning in Grade V at MI Al-Ba’ani, Bengkulu City. Methodology: This research employed a qualitative descriptive method, with the Grade V teacher and students as data sources. Data collection techniques included observation, interviews, and documentation, which were analyzed through data reduction, data display, and conclusion drawing. Findings: The results indicate that the implementation of the word guessing method in Grade V IPAS learning at MI Al-Ba’ani has been conducted in a planned and systematic manner, aligned with the principles of the Merdeka Curriculum. The teacher demonstrates a solid understanding of the word guessing method and utilizes it as a strategy to create an active, creative, and enjoyable learning environment. The learning process spans from meticulous planning and active student involvement in group activities to evaluations that assess not only the final outcomes but also the learning process, including student engagement, cooperation, and conceptual understanding. Furthermore, the word guessing method is proven to have a positive impact on enhancing students' memory. This is evident in the students' increased ability to recall terms and concepts, as the learning material is presented through interactive and meaningful game-based activities.